2010
DOI: 10.1016/j.bjps.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Where to find facial artery perforators: A reference point

Abstract: SUMMARYReconstructive surgery of the midface using facial artery perforator (FAP) flaps is being used more frequently now as it has been reported to provide better aesthetic results and reduce a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 8 publications
1
31
0
1
Order By: Relevance
“…According to a cadaveric study by Ng et al. , 2 there are multiple facial artery perforators along the facial artery, a mean of four perforators per hemiface (range, 2–8). The mean diameters of the perforators were 0.94 mm (range, 0.53–1.36 mm).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a cadaveric study by Ng et al. , 2 there are multiple facial artery perforators along the facial artery, a mean of four perforators per hemiface (range, 2–8). The mean diameters of the perforators were 0.94 mm (range, 0.53–1.36 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond 60 mm, the number of perforators decreased. However, in reality, the distribution of perforators will be much more compact as the facial artery has a tortuous course 2 . Hence, application of a perforator flap or perforator‐based flap for the reconstruction of the midface area is available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the propeller concept for flap design was first described, it has broadened freedom in flap design to help reconstruction surgeons achieve both functional and cosmetic goals. Herein, we describe an anatomical study in a Colombian population to validate (by use of cadavers) the previous vascular anatomy descriptions of the facial artery perforator in the worldwide literature, and we report on seven clinical cases.…”
Section: Introductionmentioning
confidence: 89%
“…Studies have shown that a single perforator can nourish a wide tissue area. [2][3][4] In this study, we present the application of facial artery perforator-based nasolabial flaps in various areas of the face and the obtained results.…”
mentioning
confidence: 98%